PENGUATAN SENSITIVITAS ETIS MELALUI INTEGRASI NILAI MORAL PADA MAHASISWA PENDIDIKAN EKONOMI - Purwaningsih, Endang (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
scholarly moral or ethical behavior. The purpose of this study is to discuss the issue of ethical sensitivity among economic education students who are taking introductory accounting lessons that are integrated with the moral value of honesty in learning through ethical discussions of world-famous real cases that are relevant to financial reporting material in order to increase students' ethical sensitivity. The survey method was employed in this study. Student surveys and observer assessments are used to test ethical sensitivity. The survey was given to 148 regular and APK economic education students. Descriptive analysis with means and percentages is used in data analysis. According to the findings of the study, the small group discussion technique of genuine ethical cases related to firm financial reporting increased students' ethical awareness, with the average student answer increasing by 5.16% and the average observer assessment score increasing by 2.8%. These findings suggest that including moral honesty standards into effective group discussions on situations of ethical infractions in financial reporting raises students' ethical awareness. This demonstrates that ethical sensitivity is being strengthened, which is the foundation for the shaping of students' ethical/moral behavior.